INTERGENERATIONAL TRAUMA AND AUTHORITARIAN PARENTING: A CASE STUDY OF A MOTHER WITH A HISTORY OF EMOTIONAL ABUSE AND REBT INTERVENTION - Halimatus Sadiah; Aisyatin Kamila; Ahmad Syamsul Muarif (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2026)
This study examines the transmission mechanisms of intergenerational trauma in a mother with a childhood history of emotional abuse who applies authoritarian parenting, contributing to clinical depression and suicidal tendencies in her child. Using a qualitative case study approach with in-depth interviews and thematic analysis, the study finds that childhood trauma formed two core maladaptive beliefs-the necessity of physical punishment and a negative determinism toward children from broken homes-which function as the primary cognitive mediator in the trauma transmission chain. A six-session Rational Emotive Behavior Therapy (REBT) intervention proved effective in disputing these irrational beliefs, improving the mother's emotion regulation, and enhancing the quality of her relationship with her child. These findings underscore the importance of assessing parenting beliefs in clinical intervention and offer an evidence-based model for breaking the intergenerational trauma cycle within Indonesian family contexts.